Polymeric nanomaterials encapsulating fluorescent polyindole-nido- carborane: design, synthesis and biological evaluation - Cao, Jia; Jin, Tao; Shao, Shihe; Mao, Boneng; Feng, Jin (Frontiers in Chemistry, 2024)
The water-soluble nido-carborane was prepared by alkali treatment of o-carborane. A polymer PInd containing a polyindole structure was synthesized and employed to label the modified o-carborane.Subsequently, four polymeric nanomaterials were synthesized with the objective of encapsulating them in order to enhance its bioavailability. The experimental results showed that the fluorescent complex encapsulated by the pH-sensitive polymer A had the best UV absorption and fluorescence intensity, and thus A-PInd-C was chosen for subsequent experiments. The TEM images revealed that the compounds exhibited a rounded internal morphology, with the layers exhibiting a tightly stacked arrangement. The AFM imaging revealed that the surface of the sample exhibited a relatively uniform and smooth appearance. In vitro release experiments conducted under acidic conditions demonstrated that A-PInd-C was released in a predominantly linear manner, with a maximum release rate of 80% observed within 48 hours. Cellular imaging experiments showed that the compound could enter HeLa and HCT-116 cells and was mainly distributed around the nucleus, especially in the acidic environment. The results of the cell proliferation toxicity experiments demonstrated that A-PInd-C exhibited inhibitory effects on HeLa, PC-3 and L02 cells. Among these, the inhibitory effect on PC-3 cells was the most pronounced, reaching up to 70%. In conclusion, this paper solves the problem of poor bioavailability of carborane by improving the boron containing compounds and also makes the system have potential for BNCT.